Gerakan Perlawanan Body Shaming melalui Musik Video Lagu Berhak Bahagia - Silvina Wahyu Febriyani; Zahrotus Sa'idah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research was motivated by the many acts of body shaming that attack women. The emergence of society's views regarding ideal body image encourages people, whether consciously or not, to compare themselves with other people. Women's space for movement becomes narrow due to patriarchy which regulates men in a dominant position while women are in a subordinate position. This is why women experience body shaming more often than men. The impacts range from a person's lack of self-confidence to mental disorders. Basically everyone can be a target for body shaming, such as Aurel Hermansyah. Aurel Hermansyah experienced body shaming through social media comments when she was pregnant with her first child because she was considered to have changed her body shape. The negative comments given to Aurel Hermansyah made Atta Hlilintar release a song entitled Berhak Bahagia. Therefore, this research aims to determine the form of resistance of the anti-body shaming movement in the song Berhak Bahagia. Using qualitative methods with a critical approach. The data collection techniques used were observation, literature study and documentation.